If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -85 = -5 + -7 Reorder the terms: -85 + x = -5 + -7 Combine like terms: -5 + -7 = -12 -85 + x = -12 Solving -85 + x = -12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '85' to each side of the equation. -85 + 85 + x = -12 + 85 Combine like terms: -85 + 85 = 0 0 + x = -12 + 85 x = -12 + 85 Combine like terms: -12 + 85 = 73 x = 73 Simplifying x = 73
| 24a-12ab= | | X^2+9x-234=0 | | 3x-4y-16=o | | -2/3*-3+5 | | (-2/3x-3)+5 | | X/5=49 | | x+4-2x=14 | | 1/4(x+2)-2=0.5 | | -2/3x-3+5 | | 7=-2/3x-3+5 | | -3=-2/3x+5 | | 10x=16+4x | | 10x-10=4x-10 | | (6)4+25= | | R/2=9 | | 4x+56=18x | | 9w-13x=25 | | 4-(y+9)=10 | | w=-275(2(1)-7) | | 15x-10-6x=1 | | Y=50x+1 | | 5(3x-2)6x=1 | | -12x+3y=-9 | | 4=-7x+4(x-2) | | 17-x=1/3(15+6) | | 3(x-3)+x=2x-1 | | 10-1x=50 | | 1/2x+10=-104x+54 | | 11+(2x-8)= | | 78+78n=546 | | 78+n=84 | | x+4=2x-28 |